Methods of using game techniques at the English language lessons in secondary school - Timoshenko, V.I.; Kostina, E.A. (KSU Publ., 2017)
The article describes the peculiarities of teaching English for students in secondary school. The authors emphasized the most important tasks that a modern foreign language teacher faces i.e. how to implement the effectiveness of game techniques in teaching students foreign languages, increase students’ interest in the language being studied, and enrich the content of foreign language education in secondary schools. Considering the peculiarities of teaching English, it is necessary to identify possible problems arising in the studying process, as well as the solution of these problems in order to make the learning process the most effective. The teaching game is the main activity in teaching foreign language at school, as it creates a favorable atmosphere for effective mastering of the educational material, the work of students in the team and independently, develops the skills of foreign language communication, and also contributes to the mental and psychological development of the child. The game method of teaching a foreign language can be used at any stage of learning, taking learners’ age features into consideration. The use of game techniques is designed to help students accept English as a real communication tool and become a useful experience in the possession of a foreign language. The authors presented ways for learners’ motivation for studying English, different game methods for language skills development of students in secondary school; the practical material is analyzed.
Жоғары мектепте ағылшын сабақтарында ойын əдістерін пайдалану əдістемесі
Методика использования игровых приёмов на уроках английского языка в средней школе
Keywords: teaching game; the English language learning; communication; language skills; teaching methods; secondary school; lessons; foreign language; learners; playing techniques